(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Methotrexate (MTX), a stoichiometric inhibitor of dihydrofolate reductase, is a chemotherapeutic agent for treating a variety of neoplasms. The objective of the present study was to synthesize nanoparticles of MTX using hyaluronic acid-polyethyleneglycol-polycaprolactone (HA-PEG-PCL) copolymer for tumor targeting. Targeting efficiency of HA-PEG-PCL nanoparticles was compared with non-HA-containing nanoparticles polycaprolactone. The copolymers were chemically synthesized and characterized by IR and Nuclear Magnetic Resonance (NMR) spectroscopes. The nanoparticles were characterized for shape and morphology by transmission electron microscopy (TEM), particle size, percentage of drug entrapment and in-vitro drug release profile. Differential scanning calorimetry (DSC) and X-ray diffraction (XRD) studies were also performed to appraise the crystalline or amorphous nature of MTX inside the polymer matrix. Formulations were prepared using different MTX: polymer ratios (1:0.05-3:0.15 w/w) and the optimum formulation with the drug: polymer ratio of 1:0.05 showed the mean particle size of 185 ± 2.21 nm and entrapment efficiency of 93.16 ± 2.1% in the case of HA-PEG-PCL nanoparticles, while the values were 140 ± 1.24 nm and 90.12 ± 1.3%, respectively, in the case of PCL nanoparticles. The nanoparticles prepared using copolymers HA-PEG-PCL showed their potential to sustain the MTX release. MTX-HA-PEG-PCL nanoparticles showed 95.08 ± 2.50% release of MTX in 96 hours while MTX-PCL nanoparticles released almost 100% of the drug in the same duration. The stability was evaluated in terms of particle size and residual drug content, the nanoparticles formulations were found to be more stable at 5 ± 3°C and then 40 ± 2°C. These results suggest that HA-PEG-PCL nanoparticles could be an efficient delivery system for MTX for targeted therapy of cancer.